POLITIK DAN BIROKRASI : NETRALITAS BIROKRASI KOTA SEMARANG PADA PEMILU LEGISLATIF DAN PEMILIHAN PRESIDEN 2014 - Lestari, Puji (Forum Ilmu Sosial, 2014)
The research about bureaucratic neutrality is feasible, considering that as a merit system bureaucracy, it is often found that a political bureaucracy (not neutral). This research was conducted in government bureaucracy of Semarang city. This is about; how bureaucratic neutrality of Semarang can be implemented on legislative and presidential elections in 2014? And if found non-neutrality of bureaucracy Semarang, what factors influence the attitudes and behavior of bureaucrats Semarang? The research was conducted with a qualitative approach to investigate PNS (civil servants) at the Department of Education of Semarang and in the District of Gunungpati. The data showed that the neutrality of Semarang bureaucracy is not good. In the legislative elections in the city of Semarang still found a violation of MenPAN Circular No 07 of 2009 and Government Regulation No. 53 of 2010 about discipline PNS. Neutrality of Semarang bureaucratsinfluenced byinternalfactorsandexternalfactors.